2016
DOI: 10.1530/eje-16-0224
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic adrenocortical carcinoma located in the ovary

Abstract: Aim: Ovarian corticosteroid-producing tumors are exquisitely rare. Our aim was to describe the first case observed in our practice. Case history: A 34-year-old female was referred for Cushing's syndrome (CS) occurring in the postpartum period. Clinical examination showed severe CS with diabetes mellitus, hypertension, and a large mass in the right lower abdomen. Biochemistry demonstrated corticotropin (ACTH)-independent CS (cortisol = 1900 ng/mL (n = 50-250), ACTH < 10 pg/mL (n = 20-46)) with estradiol and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…All of the above is consistent with the malignant nature of this tumor. Immunohistochemical studies confirmed the tumor cells' steroidogenic capability as they were immunopositive for calretinin, inhibin, vimentin, melanoma antigen recognized by T cells-1, and synaptophysin (5,7). Immunohistochemical studies were also useful to differentiate the tumor from renal cell carcinoma as the tumor was immunonegative for cytokeratin and CD 10, markers that are found in renal cell carcinoma (7).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…All of the above is consistent with the malignant nature of this tumor. Immunohistochemical studies confirmed the tumor cells' steroidogenic capability as they were immunopositive for calretinin, inhibin, vimentin, melanoma antigen recognized by T cells-1, and synaptophysin (5,7). Immunohistochemical studies were also useful to differentiate the tumor from renal cell carcinoma as the tumor was immunonegative for cytokeratin and CD 10, markers that are found in renal cell carcinoma (7).…”
Section: Discussionmentioning
confidence: 79%
“…Tumors arising from adrenal remnants are usually scarce. They are often benign and non-functioning (5). Primary ACC is also rare with an incidence of 0.5 to 2 per million annually (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations